Ways of increasing the effectiveness of junior pupils’ self-preparation in the conditions of extended daycare groups - Білоконна, Ніна Іванівна; Кравцова, Інна Адамівна (Pedagogy of Higher and Secondary Education, 2019)
Belokonnaya N. I., Kravtsova I. A. Ways of increasing the effectiveness of junior pupils’ self-preparation in the conditions of extended daycare groups. The article deals with the problem of a professional development of a daycare group teacher. The authors have offered recommendations how to masters self-preparation as an important regime moment of the extended daycare group. They have also given the characteristic of conditions to promote the formation of junior pupils’ self-dependence. The fulfillment of these conditions ensures the quality of homework and also influences positively upon the total development of each pupil as a personality. Establishing the subject- subject interaction during self-preparation will allow the pupils to realize actively the importance of self-dependent gaining of knowledge and will make the pedagogical process in the extended daycare group more efficient and harmonious.